Resolusi Konflik berbasis Syura sebagai Strategi Manajemen Preventif untuk Mengurangi Bullying di Pesantren - Mohammad Syifaur Rizal (CV. Laskar Karya, 2025)
Bullying in Islamic boarding schools (pesantren) has become a significant social issue, disrupting both harmony and the learning process among students (santri). This study aims to analyze the implementation of syura-based conflict resolution as an effort to reduce bullying behavior at Pondok Pesantren Nurul Jadid. The research employs a qualitative case study approach involving three key subjects: the Head of Pesantren Affairs Bureau, the Head of Counseling and Dormitory Affairs (BKWA), and santri guardians. Data were collected through in-depth interviews, participatory observation, and documentation review. Thematic analysis was used to interpret the findings. Results show that the syura approach, rooted in Islamic values of dialogue and collective decision-making, creates a conducive communication space, increases empathy, promotes social responsibility, and restores strained relationships among santri. The novelty of this study lies in its use of a collective, dialogic, and restorative approach in addressing bullying—moving beyond individual counseling or punitive strategies. The implications suggest that integrating syura-based resolution mechanisms can enhance school management systems by fostering safer, more harmonious learning environments within pesantren.